Estimated capital stock values for German manufacturing enterprises covered by the cost structure surveys - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2010)
Information on the capital stock employed in a firm is missing in data sets from official statistics in Germany. This paper presents a method to estimate the capital stock of manufacturing enterprises that are covered by the cost structure survey from German official statistics. It uses data from this survey on the amount of depreciation at the enterprise level, information on the average life span of capital goods (for equipments, and for buildings) at the level of the economy , and information on the composition of the capital stock at the level of two-digit industries. The paper reports the data needed to estimate the capital stock at the enterprise level for the years 1995 to 2008. The appendix gives the Stata code to compute these estimates.
Keywords: C81; 330; enterprise data; Germany; capital stock data; cost structure survey; Betriebliches Anlagevermögen; Schätzung; Kostenstruktur; Statistik; Verarbeitendes Gewerbe; Deutschland